ANALISIS KEPATUHAN PEKERJA TERHADAP PENGGUNAAN ALAT PELINDUNG DIRI (APD) (StudiKasus Area Produksi di PT. X ) - Vita Insani Saragih; Bina Kurniawan; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
PT. X is a company that working in the area of production of animal feed who in the production involved many workers. In implementing production process, workers should use personal protective equipment according to their indivto keep safety and health workers. This study aims to analyze the compliance level of workers on the use of personal protective equipment in the area firm production. This research is the qualitative study descriptive by observation and in-depth interviews with informants and content analisysis .The subject of study were 7 workers of production line and 3 people as informants triangulation the chairman and secidual risk retary of committee trustees occupational health and safety and leader of production line .The results of research showed that production line workers have a good knowledge and understand the usefulness of the personal protective equipment , having nice perception about the importance of the personal protective equipment , as well as having attitude and positive responses about personal protective equipment .Workers were not use personal protective equipment routine .Socialization had done by the company the last time done in late 2015.Provision personal protective equipment by the company still not good for workers .The company does not have reward program and punishment aboutthe occupational safety and health. Rewards only to a worker example and punishment for workers who smoke in outside smoking .Companies should improve socialization and supervision to discipline workers to be followedfollowed in using about personal protective equipment at work.